Innovation Through AI Integration: A Study Of AI Technology Adoption For The Maritime Inspection And Consulting Sector Using Soft System Metodology - Suprajeni, M Raihan (International Journal of Business Studies, 2025)
The maritime industry, a global powerhouse for trade and transportation, is on the cusp of a transformative era driven by Artificial Intelligence (AI). This paper explores the potential of AI to revolutionize various aspects of the maritime sector, from navigation and route optimization to predictive maintenance and enhanced safety. In this paper, AI implementation in inspection and consulting industry will be studied, this AI will help fasten regulatory compliance process and maintenance services in maritime Industry. The study showed that there are four main stakeholders in AI implementation, which are Operational expert, Managers, Clients, and AI team. Each stakeholder has a crucial part to play in the successful implementation of AI in this industry. This study will map out the interest of each stakeholder using SSM, therefore giving a clear picture of what each stakeholder wants and their apprehensions. The result of this study is some conditions that need to be met by each stakeholder for the implementation of AI in this sector to be successful.